2018
DOI: 10.1090/tran/7326
|View full text |Cite
|
Sign up to set email alerts
|

On the honeycomb conjecture for a class of minimal convex partitions

Abstract: Abstract. We prove that the planar hexagonal honeycomb is asymptotically optimal for a large class of optimal partition problems, in which the cells are assumed to be convex, and the criterion is to minimize either the sum or the maximum among the energies of the cells, the cost being a shape functional which satisfies a few assumptions. They are: monotonicity under inclusions; homogeneity under dilations; a Faber-Krahn inequality for convex hexagons; a convexity-type inequality for the map which associates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Finally, relying on Theorem 2 and using a blow-up argument, we obtain that the honeycomb conjecture for the Cheeger constant holds true for every Lipschitz domain Ω in the following asymptotic form (which is exactly the same as in [3], without the convexity assumption on the cells): , β). Precisely, given β > 0 (fixed), λ 1 (Ω j , β) is the lowest positive number for which the equation…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Finally, relying on Theorem 2 and using a blow-up argument, we obtain that the honeycomb conjecture for the Cheeger constant holds true for every Lipschitz domain Ω in the following asymptotic form (which is exactly the same as in [3], without the convexity assumption on the cells): , β). Precisely, given β > 0 (fixed), λ 1 (Ω j , β) is the lowest positive number for which the equation…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 79%
“…More recently, problems of the kind (1) and (3) have been studied in [3], where it is shown that, under the a priori requirement that all the cells of the partitions are convex, the honeycomb conjecture holds true under the form (4) lim k→+∞ |Ω| 1/2 k 1/2 M k (Ω) = h(H) , lim k→+∞ |Ω| 1/2 k 3/2 m k (Ω) = h(H) , where H denotes the unit area regular hexagon. Clearly, the convexity assumption made on the cells in [3] is quite stringent.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…that can be builded along the road I, with problem (6) the builder is looking for the best position to place the facilities so as to minimize the (average or maximum) distance the people have to cover to reach the nearest facility. Theorem 2.11 then applies: for both problems the solution is unique and satisfies λ nj 1 (I j1 ) = λ nj 2 (I j2 ) for all 1 ≤ j 1 , j 2 ≤ n. Versions of these problems in higher dimension for the Laplace operator have applications to the phenomenon of the spatial segregation in reaction-diffusion systems [6,8,9,17]. By the way, many others spectral partition problems can be considered, such as the ones involving the eigenvalues of singular operators, nonlinear operators (i.e., the p-Laplacian for 1 < p < +∞), higher order operators (i.e., the bi-Laplacian) or fractional operators (i.e., the s-Laplacian for 0 < s < 1).…”
Section: Optimal Partitions For Fixed Nmentioning
confidence: 99%
“…On one side, rigorous studies of partition problems require advanced mathematical tools; on the other, optimal partitions arise in several concrete applications, such as in discrete allocation problems, in statistical decision theory, and in phenomena of spatial segregation in reaction-diffusion systems. For some works on the subject one can consult [4,6,8,9,12,13,14,17,21] and the references therein.…”
Section: Introductionmentioning
confidence: 99%